The complete chloroplast genome sequence of Melothria scabra (Cucurbitaceae) - Chan Deng; Xinbi Jia; Siyue Chen; Jiaqi Guo; Chenghong Zeng; Yuewen Chen; Qianglong Zhu; Yingjin Huang (Mitochondrial DNA. Part B. Resources)
Melothria scabra has gradually become an economically important plant worldwide. The complete chloroplast genome of M. scabra has a length of 156,744 bp, contains a large single-copy (LSC) region (86,387 bp), a small single-copy (SSC) region (18,055 bp), and two inverted repeats (IRs) with the same length of 26,151 bp. In total, 126 genes were detected, including 83 protein-encoding genes, 35 transfer RNA (tRNA) genes, and eight ribosomal RNA (rRNA) genes. For phylogenetic analysis, M. scabra has a closer genetic relationship with Cucumis sativus and Citrullus lanatus. The complete chloroplast genome sequence of M. scabra would promote the germplasm exploration, phylogenetic relationships, and molecular biology researches in Melothria.